LEGAL BASIS AND REGULATION OF ENSURING TRANSPARENCY OF COURT HEARINGS IN MILLY'S CRIMINAL PROCEEDINGS. - Adizov Alibek Oybek o’g’li; B.K. Khudaybergenov (Scholar Express Journals, 2023)
In this case, the modern best practices of open criminal proceedings in court were studied, the legal system of Uzbekistan was compared, and useful suggestions were put forward.
Keywords: Disclosure; criminal process; justice; public control